Association between HER2 status and response to neoadjuvant anthracycline followed by paclitaxel plus carboplatin chemotherapy without trastuzumab in breast cancer - Yao, Lu; Zhang, Juan; Liu, Yiqiang; Ouyang, Tao; Li, Jinfeng; Wang, Tianfeng; Fan, Zhaoqing; Fan, Tie; Lin, Benyao; Xie, Yuntao (Chinese Journal of Cancer Research; Vol 27, No 6 (December 22, 2015): Chinese Journal of Cancer Research, 2015)
Background: We recently showed HER2-positive breast cancers are less likely to respond to neoadjuvant anthracycline chemotherapy. Here, we investigated whether HER2-positive breast cancers responded to sequential neoadjuvant anthracycline followed by paclitaxel plus carboplatin regimen in the absence of trastuzumab. Methods: Women (n=372) with operable primary breast cancer initially received two cycles of neoadjuvant anthracyclines, the clinical tumor response was assessed, then patients were received four cycles of paclitaxel plus carboplatin regimen. All the patients did not received trastuzumab treatment in the neoadjuvant setting. HER2 status was determined by immunohistochemistry and/or by fluorescence in situ hybridization in corebiopsy breast cancer tissue obtained before the neoadjuvant chemotherapy. Results: Eighteen percent (67/372) of patients achieved a pathologic complete response (pCR) in their breast. HER2-positive tumors had a significant higher pCR rate than HER2-negative tumors (33.0% versus 13.5%, P